Putting the individual in the context of the organization: A Carnegie perspective on decision-making - Levinthal, Daniel A.; Newark, Daniel A. (Frontiers in Psychology, 2023)
The majority of decision research portrays decision makers as largely decontextualized, separate from the institutional and social factors that influence their choosing. On the occasions when context is considered, it is rarely organizational, despite the prominence of organizations in decision makers' lives. By contrast, the Carnegie perspective on decision making emphasizes context, particularly that of organizations, as a central concern. We develop this contrast by first reviewing the limited role of context in neoclassical economic and psychological depictions of choice. Next, we present key elements of decision context in the Carnegie perspective: decision premises, standard operating procedures and decision rules, organizational structures, learning environments, and identity-situation interaction. We then consider the importance of interpretation to decision making in context. In particular, rather than being given and clear, the meaning of decision context is often ambiguous and must be interpreted or constructed. The Carnegie perspective underscores the importance of this interpretive process to both decision making and everyday life. We conclude by considering aspects of context that merit greater examination, as well as the implications for behavioral theorizing of acknowledging the contextualized nature of action.